This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yeah so easy!
Thanks for the solution
∫ 0 π s i n x ( c o s x ) 2 = − 3 1 ( c o s 3 x ) 0 π = 3 2
Consider y=Cos^3(x), dy/dx by the chain rule is -3Sin(x)Cos^2(x), adjusting for the intended result in this question we now consider y= -(1/3)Cos^3(x), which is the desired solution as constant coefficients are invariant. Next substitute for the limits in radians and simplify.
Problem Loading...
Note Loading...
Set Loading...
let cosx=t ,-sinxdx=dt and limits change to cos0=1 and cos pi=-1. integration of [-t^2 dt] with limits 1 to -1. on solving we get -t^3/3. after putting limits 2/3=0.667